1976
DOI: 10.1017/s0022112076002711
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetric flow of a viscous fluid near the vertex of a body

Abstract: Axially symmetric motion of a viscous fluid in a cone is considered on the basis of the Stokes assumption. Near the apex of the cone the solution obtained reveals features quite similar to those of that near a sharp corner in two dimensions, which has been discussed already. An infinite sequence of eddies is induced near the apex for values less than about 80·9° of the semi-angle of the cone, which is measured from the symmetry axis lying in the fluid. The solution found by Pell & Payne for a spindle in a unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 11 publications
5
28
0
Order By: Relevance
“…Both Wakiya (11) and Liu & Joseph (12) have studied this geometry and demonstrated the formation of axisymmetric eddies. Malyuga (13) and Shankar (14) have extended these results to consider fully three-dimensional flows.…”
Section: Introductionmentioning
confidence: 99%
“…Both Wakiya (11) and Liu & Joseph (12) have studied this geometry and demonstrated the formation of axisymmetric eddies. Malyuga (13) and Shankar (14) have extended these results to consider fully three-dimensional flows.…”
Section: Introductionmentioning
confidence: 99%
“…Wakiya [13] revealed that the eddies exists in a cone whose half-angle  (i.e., the angle between the axis and the sidewall) is less than 80.9. This feature of conical flows is important for our study, where  = 30, 45 and 60.…”
Section: Introductionmentioning
confidence: 98%
“…Fig. 2(a) It is known that a single-fluid flow (e.g., with no water) has a cascade of eddies with alternating circulation directions [13]. The dimensions and strengths of eddies tend to zero as the cone tip is approached.…”
Section: Bifurcations At  = 30mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from (6.4) and (6.5), the rescaled velocity must satisfyŨ t = −ŪX and V t =V atX = −∞ andŨ t = V t = 0 atX = ∞, the leading-order boundary conditions obtained by neglecting in (6.6) and (6.7) terms that vanish when Re a → 0. With a zero mass flux, the leading-order solution must show forX → ∞ a velocity that decays withX at an exponential rate, eventually giving rise to the Stokes toroidal vortices described by Wakiya (1976). This leading-order description can be expected to fail asŨ t decays to values of order Re a , where the mass flux should be taken into account, eventually leading to either the Poiseuille profile or a uniform velocity profile.…”
Section: Leading-order Solutionmentioning
confidence: 99%